2018
DOI: 10.22159/ajpcr.2018.v11i3.22105
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Novel Drug Targets in Acinetobacter Baumannii by Subtractive Genomic Approach

Abstract: Objective: Multiple drug resistance (MDR) in bacteria, particularly Gram-negative bacilli, has significantly hindered the treatment of infections caused by these bacteria. This results in the need for identifying new drugs and drug targets for these bacteria. The objective of this study was to identify novel drug targets in Acinetobacter baumannii which has emerged as a medically important pathogen due to an increasing number of infections caused by it and its MDR property.Methods: In our study, we implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…These 7 pathways include a two-component system, bacterial secretion system, Quorum sensing, Monobactam biosynthesis, metabolism of microbe within diverse environments, and synthesis of the secondary metabolites. The findings of pathways identification which are specific to the pathogen are in line with the results of L. interrogans , A. baumannii, and S. saprophyticus reported by ( Amineni et al, 2010 , Goyal et al, 2018 , Shahid et al, 2020 ). A total of 16 essential proteins of S. sonnei were associated with these 7 pathways.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These 7 pathways include a two-component system, bacterial secretion system, Quorum sensing, Monobactam biosynthesis, metabolism of microbe within diverse environments, and synthesis of the secondary metabolites. The findings of pathways identification which are specific to the pathogen are in line with the results of L. interrogans , A. baumannii, and S. saprophyticus reported by ( Amineni et al, 2010 , Goyal et al, 2018 , Shahid et al, 2020 ). A total of 16 essential proteins of S. sonnei were associated with these 7 pathways.…”
Section: Discussionsupporting
confidence: 90%
“…The subcellular location of the DnaA was identified using Psortb. The subcellular location of protein helps in determining the protein function as well as its potential as a potent target ( Goyal & Citu, 2018 ). DnaA was found to be cytoplasmic protein as predicted by Psortb.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subcellular localization prediction provides a fast and relatively cost-effective method of obtaining information regarding the function of a particular protein. Moreover, it was found that proteins can localize at multiple sites, therefore localization is a critical aspect of designing any therapeutic agent [28]. Cytoplasmic proteins are considered more suitable as drug targets because proteins located on the membrane are difficult to purify and analyze [26].…”
Section: Subcellular Localization Predictionmentioning
confidence: 99%
“…As a result, targeting such genes may prove fatal and disrupt human metabolism. Selection of non-homologous proteins not found in Homo sapiens can reduce the risk of adverse events and cross-reactivity [54]. We screened 145 non-homologous proteins to avoid such unfavorable situations and toxicity.…”
Section: Discussionmentioning
confidence: 99%